Membentuk Karakter Kepemimpinan dan Kemandirian pada Siswa Boarding School dengan Strategi Musyrif - Muhammad Khairul Basyar (Alignment:Journal of Administration and Educational Management, 2020)
This study aims to determine the Musyrif strategy applied in the formation of leadership and independence character in SMA Insan Cendekia Mandiri Boarding School (ICMBS), Sidoarjo. This study uses a qualitative descriptive approach, data obtained through observation, documentation and in-depth interviews. Sources of data in this study were obtained through interviews on January 29 - February 7 2020 together with the Supervisior of the High School Dormitory, Musyrif, and board of the Santri Boarding Organization and SMA ICMBS Alumni as supporting data. The collected data were analyzed using descriptive analysis techniques. The results showed that in character building, the musyrif strategy is divided into two, namely (a) internal strategy includes six stages - planning, introduction, implementation, supervision, reward and punishment, and evaluation, and (b) external strategies namely introduction, supervision, and integrated evaluation through active communication with guardian parents in both formal and informal forms. So, it can be concluded that the musyrif strategy is very effective in shaping the character of leadership and student independence. Keywords: Musyrif Strategy, Leadership Character, Independence Character